HAWT Design and Performance Evaluation: Improving the BEM Theory Mathematical Models. (December 2015) - Lanzafame, R.; Mauro, S.; Messina, M.
Abstract: This paper presents an improved numerical code based on BEM theory, implemented to evaluate the performance of a HAWT (Horizontal Axis Wind Turbines). This numerical code is a 1-D code characterized by fast processing times and reliable results. The critical aspects of the codes based on the BEM theory are widely known in scientific literature. In this paper, the authors explain how to resolve these aspects. One of these is represented by the radial flow along the blades. Radial flow is a 3-D flow, but can be dealt with inside a 1-D code only using a mathematical expedient. This expedient was tested and validated for the Risø test turbine LM 8.2 (with the NACA 63x -2xx airfoil series along the blades). Radial flow along the blades is taken into account, thus increasing the experimental C L distribution in the stalled aerodynamic region, based on CFD 3D results. The mathematical equation adopted to describe the C L distribution of the NACA 63x -2xx airfoil is a fifth order logarithmic polynomial. With this numerical code, the mechanical power curve of the Risø test turbine has been calculated, and then compared with the experimental curve found in scientific literature.